Journey to Digital Route... The Oman Collection - Sharma, Nidhi (2024)
Keywords: Emigration -- Inde -- Oman

Ratansi Purshottam, the Gujaratis of Muscat, and the Global Connectivity of Indian Ocean Transregional Markets - Allen, Jr, Calvin H. (Transregional Trade and Traders: Situating Gujarat in the Indian Ocean from Early Times to 1900, 2019)
This chapter provides a case study of the career of Seth Ratansi Purshotam to demonstrate the role of Gujarati Banyans of Muscat, Oman in linking that port’s transregional commercial network of India, the Persian Gulf, and East Africa to the global market. Ratansi, a native of Mandvi, Kachhch, began his career as a clerk in his uncle’s shop in 1857, opened his own shop in 1867, and by the 1880s until his death in 1904 was one of the leading importers/exporters and money lenders of Muscat and a principal financier of the government of Oman as the customs farmer. During that period Ratansi joined with other Banyan, Khoja, and Arab merchants to expand and strengthen direct contacts with European and American commercial outlets for the export of Omani products, especially dates, and the import of Western manufactured consumer goods, most notably arms and ammunition.
Keywords: Emigration -- Inde -- Oman